2018
DOI: 10.1080/19401493.2017.1417483
|View full text |Cite
|
Sign up to set email alerts
|

On the multi-agent stochastic simulation of occupants in buildings

Abstract: One of the principle causes for deviations between predicted and simulated performance of buildings relates to the stochastic nature of their occupants: their presence, activities whilst present, activity dependent behaviours and the consequent implications for their perceived comfort. A growing research community is active in the development and validation of stochastic models addressing these issues; and considerable progress has been made. Specifically models in the areas of presence, activities while prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 75 publications
0
39
0
Order By: Relevance
“…(Perrels and Weber, 2000) analysed the impact of lifestyles determined by socio-demographic variables (age, income, education level) on energy demand and demonstrated that final energy consumption for a stagnation-type household is 1.5 times higher than for a sustainable through reflective consumption household. Furthermore, social interactions are an essential consideration (Chapman, 2017) since they lead to decisions on a household level (e.g., opening windows) that differs from what an agent alone would choose (e.g., occupant bothered by the cold).…”
Section: Towards Human-centred Building Designmentioning
confidence: 99%
See 1 more Smart Citation
“…(Perrels and Weber, 2000) analysed the impact of lifestyles determined by socio-demographic variables (age, income, education level) on energy demand and demonstrated that final energy consumption for a stagnation-type household is 1.5 times higher than for a sustainable through reflective consumption household. Furthermore, social interactions are an essential consideration (Chapman, 2017) since they lead to decisions on a household level (e.g., opening windows) that differs from what an agent alone would choose (e.g., occupant bothered by the cold).…”
Section: Towards Human-centred Building Designmentioning
confidence: 99%
“…However, these platforms may hinder coupling with other existing physical models. The decision-making process is based on probabilities in forty per cent of the studies (Alfakara, 2010;Azar and Menassa, 2010;Tröndle and Choudhary, 2017;Abdallah, Basurra and Gaber, 2018;Chapman, Siebers and Robinson, 2018).…”
Section: Literature Review On Existing Abms For Occupants' Behaviour mentioning
confidence: 99%
“…They compared Haldi's shade model with other schedule and rule-based shade models, however, this research did not consider cooling and heating energy uncertainty. A few researchers [21,22] simulated building energy performance by considering different occupant behaviors (such as window opening, shade adjustment, and occupancy), however, the energy uncertainty resulting from manual shades alone cannot be directly obtained from these studies since they only gave the overall impact of different occupant behaviors. Additionally, they all used Haldi's shade model, which is an unusual shade configuration, as mentioned above.…”
Section: Yearmentioning
confidence: 99%
“…Therefore, the Monte Carlo analysis was adopted to analyze the uncertainty of energy performance. As described in [22], additional simulation time needed for Monte Carlo can be considered as a weakness. Thus, this study calculates the required minimum number of simulations according to the graphical method recommended in [25].…”
Section: Number Of Repeated Simulationsmentioning
confidence: 99%
“…Noteworthy studies that try to combine multiple aspects to derive a simulation framework are rare (Chapman, Siebers, and Robinson 2014;Rysanek and Choudhary 2015;Tanimoto, Hagishima, and Sagara 2008). However, those that do exist tend to adopt one complexity level for all aspects of OB, without considering their relative importance.…”
Section: Introductionmentioning
confidence: 99%